SELECTIVE PARENCHYMA CLAMPING TECHNIQUE AS AN ALTERNATIVE TO TRADITIONAL VASCULAR CLAMPING DURING PARTIAL NEPHRECTOMY - M. S. Mosoyan; S. K. Al-Shukri; D. Y. Semenov; A. M. Essaian; D. M. Ilin (Вестник урологии, 2014)
The aim of our study is to introduce a safe and easy way to perform partial nephrectomy via different approaches with a set of our specially engineered instruments for parenchyma clamping. Between January 2011 and October 2013 we performed a total number of 110 open, laparoscopic and robotic partial nephrectomies (PN) in patients with RCC stage T1-2N0M0. Eighty-six and 24 patients underwent PN with traditional vascular clamping (VC group) and selective parenchyma clamping (PC group), respectively. We worked out 3 types renal parenchyma clamps (patented inventions): one for laparoscopic/robotic PN and two kinds for open procedures (upper/lower pole and middle segment of kidney). We measured glomerular filtration rate (GFR) before the procedure and 24 hours and 1 year after. We also measured operative time, blood loss, warm ischemia time and parenchyma clamping time. In VC group depression of GFR 24 hours and 1 year after the operation was 22% and 33%, respectively. Deterioration of GFR 24 hours and 1 year after surgery in PC group was 5% and 12%, respectively. In both groups patients didn’t face any perioperative complications or reinterventions. Cancer-specific survival rate was 100% in both groups during 1 year follow-up. NSS can be performed in a safe manner under regional ischemia with selective parenchyma clamping. Regional ischemia shows better functional results immediately and 1 year after the surgery and can be achieved by using specially designed parenchyma clamps during open, laparoscopic and robotic partial nephrectomy.